Change of patient-reported aesthetic outcome over time and identification of factors characterizing poor aesthetic outcome after breast-conserving therapy: long-term results of a prospective cohort study - Hennigs, André; Biehl, Hannah Maria; Rauch, Geraldine; Golatta, Michael; Tabatabai, Patrik; Domschke, Christoph; Schott, Sarah; Wallwiener, Markus; Schütz, Florian; Sohn, Christof; Heil, Jörg (Annals of surgical oncology, 2016)
We analyzed the change of aesthetic outcome (AO) over time and explored factors characterizing poor AO after breast-conserving surgery (BCS).
Published online: 6 November 2015
Gesehen am 12.05.2020